Three New Delphiniums from Turkey - Tan, Kit; Ilarslan, R. (Edinburgh Journal of Botany, 2010)
Three more new species of Delphinium (Ranunculaceae) belonging to sect. Delphinastrum DC, are described and illustrated from S and NE Anatolia: D. petrodavisianum, D. kitianum and D. iris.